Bronze medal in INDES 2018: Building lectures / Nor Azizah Talkis - Talkis, Mor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
A team of innovative lecturers including, Muhammad Redza Rosman, Hafizah Mohd Latif, muhammad Naim Mahyuddin, Noor Sahidah Samsudin and Rafizah Mohamed Nordin won a bronze medal in the International Innovation, Invention and Design Competition (INDES) 2018 which was held on August 15, 2018.